Prognostic factors for the clinical outcome of patients with follicular lymphoma following high-dose therapy and peripheral blood stem cell transplantation (PBSCT) - Voso, Maria Teresa; Martin, Simona; Hohaus, Stefan; Abdallah Khalafallah, Alhossain; Schlenk, Richard Friedrich; Ho, Anthony Dick; Haas, Rainer (Bone marrow transplantation, 2000)
This is a report on 111 patients with advanced stage follicular lymphoma who where autografted using PBSC. Seventy patients were enrolled in first remission, whereas 41 were treated in second or higher remission. High-dose therapy consisted of total body irradiation plus cyclophosphamide in 103 patients, while eight patients received BEAM (carmustine, etoposide, cytosine-arabinoside, melphalan). Autografts contained 8.1 ± 0.6 × 106 CD34+ cells/kg body weight. At a median follow-up of 44.2 months from PBSCT (range 4.9-77.4 months), 93 patients are alive, with a probability of overall and relapse-free survival (RFS) of 83% and 64%, respectively. A significantly higher probability of relapse was associated with male gender, involvement of more than eight lymph node areas, extra-nodal manifestations other than bone marrow and PBSCT performed in second or higher remission. In the latter group of patients, previous radiotherapy was associated with poor prognosis. The relevance of chemosensitivity as a prognostic factor was reflected by a better RFS in patients who had achieved complete remission at the time of PBSC mobilization. In a multivariate analysis, involvement of eight or more lymph nodes and high-dose therapy performed in second or higher remission were independent prognostic factors. Bone Marrow Transplantation (2000) 25, 957-964.
Gesehen am 21.12.2021